Distribution of filled, decayed and missed teeth in North West of Tehran - Eshraghian MR; Kanzali B (Tehran University of Medical Sciences, 1998)
The purpose of this article is to study distribution of DMF(T) and its D,M and F protions exactllly. 1500 subjects were examined clinicaly. They were 5 to 70 years old, with average 24 years. Only cavitated and coronal dental caries included in this research. The results of this study are:"n1. The caries lesions of upper and lower second permolars are equal."n2. Anterior to second premolars, the DMF(T) of upper jaw teeth is higher than lower jaw's one. Conversely posterior to second premolars, lower jaw teeth has higher DMF(T)."n3. Deciduous teeth of females have lower DMF(T)."n4. Permanent teeth of females have higher DMF(T)."n5. The upper Canines of females are exceptions. Upper canines of females have lower DMF(T) than males' ones."n6. It seems that sex hormones influence DMF(T) through Saliva and eruption time of teeth."n7. Susceptibility to Caries relates to microbial plaque formation and salivary protection."n8. The females have more filled teeth than males.